136 Characterizing the medical and social complexity of Inuit children, youth, and their families from Nunavut who access care at an urban tertiary level paediatric hospital – A retrospective chart review of an Inuit child health clinic. (29th October 2021) - Ge, Yipeng; Jetty, Radha; Newhook, Dennis; Webster, Richard; Mills, Amanda; McCann, Victoria; Trincao-Batra, Sara; Baba, Katherine; Sutherland, Stephanie; Reddy, Deepti
Abstract: Primary Subject area: Social Paediatrics Background: The Inuit Child Health Clinic is a consulting general pediatric outpatient clinic at an urban tertiary level paediatric designed to improve integration and coordination of care for Inuit children, youth, and their families from Nunavut. Characterizing medical and social complexity for this patient population will help to address existing gaps in health and social care, as well as contribute to the development of a culturally safe and sensitive determinants of health screening tool. Objectives: To study and characterize the complexities that families cared for by the Inuit Child Health Clinic experience in navigating the health and community environments to identify gaps that exist within their care and understand how we can better support their unique needs. We define medical complexity similarly, referenced in existing literature as multi-system or multi-service involvement or prolonged stay in the city of the urban tertiary level paediatric hospital to access medical care. Design/Methods: A retrospective chart review of patients (children and youth between the ages of 0-18 years old) and their caregivers that attended an outpatient general paediatric medicine clinic visit appointment with the Inuit Child Health Clinic between September 30, 2016, and September 30, 2019. A review of 59 patient charts were completed by 2 independent reviewers each for demographic information, medical complexity variables, and social complexity variables. This research has been approved by a local Research Ethics Board as well as the Nunavut Research Institute. Results: There are high levels of medical and social complexity as evident through the high average number of healthcare services accessed, number of comorbidities, and number of admissions to hospital. We also found considerable inconsistencies with respect to documentation by providers on the social determinants of health of patients. Note: In collaboration with the Inuuqatigiit Centre for Inuit Children Youth and Families, Qikiqtani Inuit Association (QIA), Nunavut Tunngavik Incorporated (NTI), and the Department of Health in Nunavut, the results and knowledge will be shared and mobilized to reflect a narrative that is community-driven and comments on any possible gaps in social determinants of health screening in clinical settings. Furthermore, in collaboration with the Qaujigiartiit Health Research Centre, this work will inform and support the broader program evaluation of the Inuit Child Health Clinic to meet the needs of patients, families, caregivers, and healthcare professionals. Conclusion: A multidisciplinary team approach that focuses on integrative care may be an effective and efficient means to promote communication and collaboration between multiple service providers that are often involved in providing care to this population that is put at-risk due to systemic health and social inequities. Improving social history taking and integrating more formal screening for social determinants of health within the Inuit Child Health Clinic practice should be considered.